Physique related perceptions and biological correlates of eating disorder risk among female collegiate equestrians - Monsma, E. V.; Gay, J. L.; Torres-McGehee, T. M. (The Journal of Performance Enhancement, 2013)
This study examined physique-related and biological predictors of eating disorder risk in a sample of 138 female collegiate equestrian athletes among whom the point prevalence risk was 42%. English (n=91) and Western (n=47) riders reported age (M=19.88 years), height, weight, age at menarche, menstrual regularity and completed the Eating Attitudes Test-26 (EAT-26), Social Physique Anxiety Scale (SPAS), and clothing-based items associated with the Stunkard Silhouette Scale. Mean comparisons indicated homogeneity between riding discipline in all variables. Correlation analyses showed riders who perceived themselves as larger (Body Image>BMI) had significantly higher SPAS and EAT- 26 scores. BMI, body image dissatisfaction in daily clothing, and SPA all contributed significant, unique variation in EAT-26 scores; Body image dissatisfaction and SPA contributed more than BMI. Implications of these findings in a sample with particularly low BMI scores suggest practitioners should focus on self-perception management strategies. Researchers are encouraged to continue examining body image distortion relationship in samples with a wider range of BMI.